2016
DOI: 10.1371/journal.pone.0165296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrofluoric Acid Etching Time on Titanium Topography, Chemistry, Wettability, and Cell Adhesion

Abstract: Titanium implant surface etching has proven an effective method to enhance cell attachment. Despite the frequent use of hydrofluoric (HF) acid, many questions remain unresolved, including the optimal etching time and its effect on surface and biological properties. The objective of this study was to investigate the effect of HF acid etching time on Ti topography, surface chemistry, wettability, and cell adhesion. These data are useful to design improved acid treatment and obtain an improved cell response. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 34 publications
2
40
0
1
Order By: Relevance
“…Mechanical anchorage to surface topographical cues, surface energy and wettability are known as factors influencing cell adhesion. In the present study, our results clearly revealed that the hydrophobic disks (D56 disks) had a significantly reduced number of adherent cells compared with the hydrophilic disks (D0 disks), which was consistent with some previous studies 20, [24][25][26] . These results illustrate one of the positive characteristics of hydrophilic surfaces and suggest that the positive effects of hydrophilic surfaces shown in previous studies can be attributed to enhanced cell adhesion capacity and the resulting cellular interactions.…”
Section: Discussionsupporting
confidence: 93%
“…Mechanical anchorage to surface topographical cues, surface energy and wettability are known as factors influencing cell adhesion. In the present study, our results clearly revealed that the hydrophobic disks (D56 disks) had a significantly reduced number of adherent cells compared with the hydrophilic disks (D0 disks), which was consistent with some previous studies 20, [24][25][26] . These results illustrate one of the positive characteristics of hydrophilic surfaces and suggest that the positive effects of hydrophilic surfaces shown in previous studies can be attributed to enhanced cell adhesion capacity and the resulting cellular interactions.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, acid etching method allows to obtain irregular and complex surface of Ti implants using strong acid solutions such as sulfuric acid (H 2 SO 4 ), hydrochloric acid (HCl), hydrofluoric acid (HF), nitric acid (HNO 3 ), and any combination of mentioned acid solutions [120]. Etching increases roughness and wettability of the implant [121] but exerts negative effect on its mechanical properties [120]. Surface modification technique combining acid-etching and sand blasting is defined as sand-blasted, large-grit, acid etched (SLA), which indicates application of an acid onto the blasted surface [120,122].…”
Section: Subtractive Modifications Of Biomaterials Surfacementioning
confidence: 99%
“…As described in a previous study, a hydrophilic surface with high surface energy might affect cell attachment and cell proliferation. Certain researchers have suggested that osteoblast cells prefer a Ti surface with negative Ssk but low roughness . In this study, group F3 revealed negative shifts, meaning that they had more valleys or pits rather than a predominance of peaks, in comparison with group F2.…”
Section: Discussionmentioning
confidence: 50%